Evaluasi Kinerja Penyisihan Kekeruhan dan Penggunaan PAC dalam Operasional Harian di SPAM Katulampa, Kota Bogor - Niesa Hanum Mistoro; Enry Adiarto Guntoro; Noviani Ima Wantoputri; Dahlia Anggita Zahra; Makmur Gunawan; Muhammad Yacob (REACTOR: Journal of Research on Chemistry and Engineering, 2026)
This study evaluates turbidity removal performance and daily Polyaluminum Chloride (PAC) use at SPAM Katulampa, Bogor, based on routine operational data under fluctuating raw water turbidity. Daily operational data from 10 February to 10 March 2026 were analysed, including raw water turbidity, treated water turbidity, PAC consumption, and flow rate. Descriptive statistics, time-series plots, turbidity removal calculation, and exploratory scatter plots with linear trendlines were used to assess treatment stability and the relationship between PAC use and turbidity. Raw water turbidity varied widely from 12.00 to 262.97 NTU, while treated water turbidity remained low at 0.52–0.91 NTU, below the 3 NTU national turbidity limit. Turbidity removal ranged from 94.9% to 99.8%, indicating stable performance of the treatment process. Daily PAC use ranged from 324.75 to 519.60 kg/day. However, the linear relationships between raw water turbidity and PAC use (R² = 0.0148), and between PAC use and treated water turbidity (R² = 0.0021), were very weak. The results indicate that low treated-water turbidity was maintained despite high raw-water variability, but this stability cannot be attributed solely to PAC use. It is more appropriately understood as the combined performance of coagulation, flocculation, sedimentation, filtration, and routine operational control. Higher-resolution operational data are needed to evaluate real-time PAC dose response and process optimization.